Effectiveness of Conservative Treatments in Positional Plagiocephaly in Infants: A Systematic Review - Maria Blanco-Diaz; Maria Marcos-Alvarez; Isabel Escobio-Prieto; Marta De la Fuente-Costa; Borja Perez-Dominguez; Elena Pinero-Pinto; Alvaro Manuel Rodriguez-Rodriguez (MDPI AG, 2023)
Objective: The objective of this study is to analyze conservative treatments implemented to manage positional plagiocephaly in infants. Methods: This is a systematic review conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, performed in the Medline (PubMed), Scopus, Web of Science, and Cochrane databases. Articles were selected according to the eligibility criteria, regarding the effectiveness of conservative treatments in positional plagiocephaly in infants, published in the last 10 years with a score ≥3 in the PEDro Scale. Results: A total of 318 articles were identified and 9 of them were finally selected. Conclusions: Physical therapy treatment is considered as the first line of intervention in plagiocephaly with non-synostotic asymmetries and manual therapy is the method that obtains the best results within this intervention. In cases of moderate or severe plagiocephaly, helmet therapy can be an effective second-line intervention; however, the best way to prevent this condition is through counseling of parents or caregivers, and early treatment is essential for optimal therapeutic outcomes. The review was registered in PROSPERO (CDR42022306466).